1991
DOI: 10.1136/bmj.303.6793.13
|View full text |Cite|
|
Sign up to set email alerts
|

Bone density in women receiving depot medroxyprogesterone acetate for contraception.

Abstract: Objective-To determine if the use of the injectable contraceptive depot medroxyprogesterone (DMPA), which reduces ovarian oestrogen production, is associated with changes in bone density.Design-Population study. DMPA Main outcome measure-Lumbar spine and femoral neck bone mineral density assessed by dual energy x ray absorptiometry.Results-Compared with premenopausal controls matched for age, race, and body mass index, DMPA users had significantly reduced bone density in the lumbar spine (mean difference 7 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
1
7

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(103 citation statements)
references
References 31 publications
4
91
1
7
Order By: Relevance
“…116 Additionally, the risk of osteoporosis associated with amenorrhea with long-term use is of concern. 117,118 Although there are no specific guidelines for teens, it is generally recommended that females who use this method for Ͼ2 years or who smoke or are extremely thin should be monitored regularly for bone density loss and be prescribed calcium supplements (1200 to 1500 mg/d). The contraceptive implant Implanon is a favorable choice for teens with compliance issues or for patients for whom pregnancy is contraindicated but who are not yet ready to undergo permanent sterilization.…”
Section: Sable Et Al Best Transition Practices For Adolescents With Chdmentioning
confidence: 99%
“…116 Additionally, the risk of osteoporosis associated with amenorrhea with long-term use is of concern. 117,118 Although there are no specific guidelines for teens, it is generally recommended that females who use this method for Ͼ2 years or who smoke or are extremely thin should be monitored regularly for bone density loss and be prescribed calcium supplements (1200 to 1500 mg/d). The contraceptive implant Implanon is a favorable choice for teens with compliance issues or for patients for whom pregnancy is contraindicated but who are not yet ready to undergo permanent sterilization.…”
Section: Sable Et Al Best Transition Practices For Adolescents With Chdmentioning
confidence: 99%
“…In contrast, some studies have failed to show the bene®t of MPA in preventing bone loss in such women [261]. In premenopausal women given progestrogens, trabecular bone loss occurs [262,263]. Dual-energy X-ray absorptiometry (DXA) measurements of the lumbar spine show progressive decreases of 2.4% at 6 months and 4.1% at 12 months [263].…”
Section: Medroxyprogesterone Acetatementioning
confidence: 89%
“…Cundy et al [6] reported a cross-sectional study of long-term DMPA users who volunteered to have their bone density measured, and found it was lower than the age-matched general population. There was no correlation between duration of DMPA use and their reduction in bone density.…”
Section: Progestogen-only Methodsmentioning
confidence: 96%